Postmarket Safety Surveillance of Delayed Complications for Recent FDA-Approved Hyaluronic Acid Dermal Fillers. Issue 2 (20th February 2022) - Cohen, Joel L.; Hicks, Jessica; Nogueira, Alessandra; Lane, Vanessa; Andriopoulos, Bill
Abstract : Supplemental Digital Content is Available in the Text. Abstract : OBJECTIVE: To review postmarketing data for delayed (≥14 days post-treatment) adverse events (AEs) of interest (inflammatory and noninflammatory nodules, hypersensitivity, granulomas) for newer hyaluronic acid (HA) fillers FDA-approved within the last 5 years (2016–2020). METHODS: Reports from the Manufacturer and User Facility Device Experience (MAUDE) database were extracted for HAREF, HADEF, HAKYS, HAVER, HAVLR, HAVOB, HARH2, HARH3, and HARH4 from January 2016 to January 2021. Keywords from event narratives were used to identify and categorize AEs and then verified through inclusion/exclusion criteria. Percentages are based on the total combined events of interest to provide an overall perspective of the events reported during the search period. RESULTS: Of 585 MAUDE reports, there were 195 (33.3%) delayed AEs of interest. Of those, 71.8% were nodules (42.1% inflammatory and 29.7% noninflammatory), 21.5% hypersensitivity, and 6.7% granulomas. The combined total events of interest, ordered by frequency reported, were HAVLR (74.4%), HAVOB (12.3%), HADEF (5.1%), HARH4 (3.6%), HAREF (2.6%), and HARH2 (2.1%), with no reports for HARH3, HAVER, and HAKYS . CONCLUSION: Although delayed nodules and inflammatory events are rare, reports for these events were extracted from the MAUDE database from 2016 to 2020 for HAVLR, HAVOB, HADEF, HARH4, HAREF, and HARH2 (most to least frequent).